Characterization of interaction and ubiquitination of phosphoenolpyruvate carboxykinase by E3 ligase UBR5 - Qingya Shen; Zhiyu Qiu; Wenping Wu; Jimin Zheng; Zongchao Jia (Biology Open, 2018)
Phosphoenolpyruvate carboxykinase (PEPCK1) is ubiquitinated by E3 ubiquitin ligase UBR5, which was thought to be facilitated by the acetylation of Lys70, Lys71 and Lys594 in PEPCK1. Here, we made a series of UBR5 HECT domain truncation variants and, through pull-down assay, showed that the N-terminal lobe of the UBR5 HECT domain is largely responsible for interacting with PEPCK1. We mutated all three lysine residues thought to be acetylated in PEPCK1 but were surprised to observe no loss of binding to UBR5 HECT domain. Furthermore, two PEPCK1 truncation variants (74-622 aa and 10-560 aa) lacking these lysine residues were still able to bind with UBR5 and ubiquitinated in HEK293T cells. To discover the ubiquitination site(s) of PEPCK1, which is currently unknown, the Lys residues of PEPCK1 were mutated to Ala and the ubiquitination level of the PEPCK1 mutants was assessed. Results revealed at least two ubiquitination sites (Lys243 and Lys342), which represent the first time that ubiquitination sites of PEPCK1 have been identified. Our pull-down experiments further show that the lack of ubiquitination of PEPCK1 Lys243Ala and Lys342Ala mutants is not due to their binding to UBR5, which remained unchanged. Taken together, our work has provided new insights into UBR5 mediated ubiquitination of PEPCK1.